Reflexões sobre as dores corporais crônicas fibromiálgicas e suas relações com a melancolia - Henriques, Carolina Cavalcanti (2013)
In contemporary practice, we have been faced with new expressions of suffering, in which the body gets featured. Among the recurring phenomena found chronic pain and fibromialgia. Studies on these subjects feature distinct positions: some consider such pain as hysterical phenomena, others as a manifestation of the body down. We intend to verify the specifics of chronic pain, since the possibility of a hysterical demonstration or depressed, but advancing the hypothesis that they may be manifestations of melancholic framework. Take the theory of Freud as the main source of our studies on the melancholy and cotejaremos also latest authors dealing with the phenomenon of pain, particularly the psychoanalytic literature. Patients who mobilized us to undertake such studies were those that were curious traits: low fluidity pulsional, dismay, pain in various parts of the body, psychosomatic symptoms, anxiety quite expressive and usually marked by a lack of sense, connoting, on the other hand, melancholic traits and somatic symptoms. In melancholy, a loss in pulsional life while suffering from a normal grief, that doesn't happen; libido peels back the object, due to a position occupied by this lost object, in which there was a double job to him directed, of love and hate, so liable to be drafted in the conscious level. In this same text, it shows that in the pathological mourning, the missing object remains invested, libidinalmente, resulting in an attachment to him, without it can be elaborated, causing therefore a shadow of the object about the subject's ego itself. That means there's a hyper narcissistic investment in object, in which the subject is fixed by pasting it. In a world facing individualism, for narcissism and without ideals is likely to stimulate more this encapsulation, preventing the subject from link. In contemporary clinical symptoms are more of this nature: are primary, narcissistic character, in which the subject finds himself wrapped in a world empty and without meaning. In this context, we think it's more conducive to speak of melancholy subjects, distinct from the depressed, because these make a libidinal investment withdrawal, but maintains a relationship with object.